2021
DOI: 10.12688/f1000research.51333.1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and compliance with Covid-19 infection prevention and control measures among health workers in regional referral hospitals in northern Uganda: a cross-sectional online survey

Abstract: Background: Infection prevention and control (IPC) has increasingly been underscored as a key tool for limiting the transmission of coronavirus disease 2019 (Covid-19) and safeguarding health workers from infections during their work. Knowledge and compliance with IPC measures is therefore essential in protecting health workers. However, this has not been established among health workers in northern Uganda in light of the Covid-19 pandemic. The objective of this study was to determine the knowledge and complia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
0
3
Order By: Relevance
“…In contrast, according to research by Hossain et al (2021), as many as 0.50% of healthcare workers in Bangladesh have poor knowledge. It is different from the results of a study by Amanya et al (2021) that found that 30.70% of healthcare workers at Regional Referral Hospitals in Northern Uganda had insufficient knowledge about COVID-19 IPC. Meanwhile, PPE knowledge is needed by healthcare workers.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…In contrast, according to research by Hossain et al (2021), as many as 0.50% of healthcare workers in Bangladesh have poor knowledge. It is different from the results of a study by Amanya et al (2021) that found that 30.70% of healthcare workers at Regional Referral Hospitals in Northern Uganda had insufficient knowledge about COVID-19 IPC. Meanwhile, PPE knowledge is needed by healthcare workers.…”
Section: Discussioncontrasting
confidence: 90%
“…The study showed that 7.00% of healthcare workers were still not compliant with PPE use. It is different from the research of Amanya et al (2021) that 32% of healthcare workers had poor adherence to COVID-19 IPC, while based on research by Neuwirth, Mattner, & Otchwemah (2020), it was found that 15% of healthcare workers who handle direct contact with COVID-19 patients have low adherence. Lack of healthcare workers' compliance with the use of PPE is related to having attended IPC Covid-19 training, having IPC guidelines, and feeling strong institutional support (Amanya et al, 2021).…”
Section: Ppe Compliancecontrasting
confidence: 62%
See 1 more Smart Citation